Projeto de antena de microfita com polarização circular para aplicação em veículos aéreos não tripulados - Araújo, Alexandre de Moraes (2018)
Demand in wireless networks has increased considerably in recent years. Consequently, the study of system components has also increased. Within this context, antennas are fundamental elements in the physical layer in radiofrequency communications, and their study has become a research area with great advances. The need in certain systems for smaller antennas and more adaptability in the space makes the microstrip antennas in potential substitutes of the traditional antennas. This work aims to find prototypes of microfite antennas that have physical and electrical characteristics, such as gain and polarization, superior to the commercial antennas of a FPV communication system (First Person View) operating at 5.8 GHz. The methodology used in this research consists of a theoretical survey about circular polarization antennas, design, simulate and construct these antennas using different substrates in order to verify their performance and to ship them in an FPV system. The results obtained through the simulation are compared with the experimental results in order to attest to the model in question based on the literature used in this work. Preliminarily, the simulated and measured results show that the Triangular Patch Antennas have all the desirable characteristics for operation in the FPV system, being possible to board them for the obtaining of images and analysis of the performance of the system